2017
DOI: 10.1242/jcs.195321
|View full text |Cite
|
Sign up to set email alerts
|

MZT1 regulates microtubule nucleation by linking γTuRC assembly to adapter-mediated targeting and activation

Abstract: Regulation of the γ-tubulin ring complex (γTuRC) through targeting and activation restricts nucleation of microtubules to microtubuleorganizing centers (MTOCs), aiding in the assembly of ordered microtubule arrays. However, the mechanistic basis of this important regulation remains poorly understood. Here, we show that, in human cells, γTuRC integrity, determined by the presence of γ-tubulin complex proteins (GCPs; also known as TUBGCPs) 2-6, is a prerequisite for interaction with the targeting factor NEDD1, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
135
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(155 citation statements)
references
References 56 publications
16
135
0
Order By: Relevance
“…It is therefore remarkable that CnnT, with its simple composition of the CM1-containing γ-TuRC recruitment/binding domain fused to a mitochondrial targeting domain, is capable of organizing robust MTOCs at the mitochondrial surface without involvement of the key PCM proteins. The small protein MOZART (MZT) [35, 36] is a direct partner of CM1 [27] that also associates with GCP3 [37] and other GCP proteins [38], and cooperates with GCP6 [39]. GCP3, in particular, may directly control conformational changes of the γ-TuRC and thus regulate its MT nucleation activity [40, 41], and MZT1 appears to be a key link [27, 38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore remarkable that CnnT, with its simple composition of the CM1-containing γ-TuRC recruitment/binding domain fused to a mitochondrial targeting domain, is capable of organizing robust MTOCs at the mitochondrial surface without involvement of the key PCM proteins. The small protein MOZART (MZT) [35, 36] is a direct partner of CM1 [27] that also associates with GCP3 [37] and other GCP proteins [38], and cooperates with GCP6 [39]. GCP3, in particular, may directly control conformational changes of the γ-TuRC and thus regulate its MT nucleation activity [40, 41], and MZT1 appears to be a key link [27, 38].…”
Section: Discussionmentioning
confidence: 99%
“…NEDD1 appears to be a γ-TuRC targeting factor [42, 43], associates with γ-TuRCs independently of CM1 in solution, and appears to anchor the γ-TuRC rather than activate it [28]. MZT1 is associated with both NEDD1-containing and CM1-containing γ-TuRCs [38]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent studies have shown that MOZART1 together with Spc110 would act as oligomerization chaperones to cooperatively promote oligomerization of γTuSCs into well‐organized and active microtubule nucleation template . Altogether, these data indicate that MOZART1 may contribute to the recruitment of γTuRCs to microtubule‐organizing centers (MTOCs), and to the activation of microtubule nucleation . Consistently, defects in MOZART1 lead to abnormalities in mitotic spindle assembly and in cell division and development …”
Section: Introductionmentioning
confidence: 72%
“…Various proteins such as pericentrin, NEDD1/GCP‐WD, and CDK5RAP2 have been implicated in the regulation of γTuRCs . In addition, recent studies revealed that MOZART1 (human mitotic‐spindle organizing protein associated with a ring of γ‐tubulin 1) protein may equally be involved in this regulation …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation